2016
DOI: 10.1101/073197
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Zika virus replication in the mosquitoCulex quinquefasciatusin Brazil

Abstract: These authors contributed equally to this work. Abstract:Zika virus (ZIKV) is a flavivirus that has recently been associated with increased incidence of neonatal microcephaly and other neurological disorders. The virus is primarily transmitted by mosquito bite, although other routes of infection have been implicated in some cases. The Aedes aegypti mosquito is considered to be the main vector to humans worldwide, but there is evidence of other mosquito species, including Culex quinquefasciatus, playing a role … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
65
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(72 citation statements)
references
References 38 publications
(30 reference statements)
1
65
0
6
Order By: Relevance
“…quinquefasciatus confirm that these mosquitoes are not competent for ZIKV transmission. Using field-collected Culex mosquitoes and ZIKV strains isolated from patients in the northeast region of Brazil as performed by Guedes et al [38], Fernandes et al [61] showed that Cx. quinquefasciatus populations were not competent for transmitting the virus.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…quinquefasciatus confirm that these mosquitoes are not competent for ZIKV transmission. Using field-collected Culex mosquitoes and ZIKV strains isolated from patients in the northeast region of Brazil as performed by Guedes et al [38], Fernandes et al [61] showed that Cx. quinquefasciatus populations were not competent for transmitting the virus.…”
mentioning
confidence: 99%
“…pipiens complex were not able to experimentally transmit ZIKV and no viral particles were detected in mosquito saliva up to 21 days after exposure to an infectious blood meal [17-20, 25, 29-36], though different results were recorded with other Cx. quinquefasciatus strains [37,38]. Even after injection of a high dose of ZIKV into the mosquito thorax, thus bypassing the midgut barrier, viral replication was reported to be poor in Culex mosquitoes and no viral particles were isolated from saliva [32] To assess the potential mechanism(s) underlying the blocking of ZIKV in Culex mosquitoes, we evaluated the ability of ZIKV to orally infect two lines of Cx.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Culex spp. are susceptible to ZIKV infection and able to effectively transmit ZIKV [34,35]. On the other hand, other studies suggest that this vector may not have competence to transmit ZIKV [18,32,33,[35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the vector competence is the innate capability to acquire and sustain the pathogen, and transmit it to a host, so many experiments on competence were performed in alternative vectors, mainly with Cx pipiens and Cx quinquefasciatus. The results showed arguments that support (Franca et al, 2016;Guedes et al, 2016;Guo et al, 2016) or reject (Aliota et al, 2016b;Amraoui et al, 2016;Boccolini et al, 2016;Fernandes et al, 2016;HallMendelin et al, 2016;Huang Y.J. et al, 2016;Weger-Lucarelli et al, 2016;Hart et al, 2017) Culex vector competence.…”
Section: Modes Of Transmission Vectorial Transmissionmentioning
confidence: 92%